PENGARUH CORPORAT GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2010 – 2016 - zahrah nabilah (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of the research is to describe (1) to find the effect of Managerial Ownership on Financial Performance (2) to find the effect of Institutional Ownership on Financial Performance (3) to find the effect of Financial Performance on Corporate Value (4) to find the effect of Managerial Ownership on Corporate Value (5) to find the effect of Institutional Ownership on Corporate. The sampling technique used is purposive sampling with criteria of LQ45 sector companies continuously enrolled during the period 2010-2015, not resulting in negative earnings, as well as companies having full data of managerial ownership, institutional ownership, PBV and ROA. The analysis technique used is classical assumption test, multiple regression analysis, path analysis, test of coefficient of determination, and hypothesis using t test partially, F test simultaneously with level of significance 5%. From the analysis results show that (1) there is no positive effect of managerial ownership on ROA (2) there is positive influence of institutional ownership to ROA (3) there is positive influence of ROA to PBV (4) there is no positive effect of managerial ownership on PBV (5) there is a positive effect of institutional ownership with PBV (6) there is no positive effect of institutional ownership on PBV through ROA.